Proton therapy in paediatric oncology: an Irish perspective - Lee, K. A.; Combs, Stephanie (Irish journal of medical science, 2017)
Background Proton therapy (PT) is a radiotherapy treatment modality that uses protons, rather than conventional photons. PT is often used in paediatric oncology due to its reported capability to...